2021
DOI: 10.1001/jamanetworkopen.2021.34290
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Costs of Postsepsis Morbidity, Nursing Care Dependency, and Mortality in Germany, 2013 to 2017

Abstract: IMPORTANCESepsis survivorship is associated with postsepsis morbidity, but epidemiological data from population-based cohorts are lacking. OBJECTIVE To quantify the frequency and co-occurrence of new diagnoses consistent with postsepsis morbidity and mortality as well as new nursing care dependency and total health care costs after sepsis. DESIGN, SETTING, AND PARTICIPANTS This retrospective cohort study based on nationwide health claims data included a population-based cohort of 23.0 million beneficiaries of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 36 publications
2
35
0
5
Order By: Relevance
“…The substantial increase in need for nursing between 3 months before and 6 months after sepsis (see Table 3) indicates the burden of disease of both sepsis survivors and their relatives as well the socioeconomic impact on society. Our findings go along with the recent German claims data analysis by Fleischmann-Struzek et al, finding 31.5% (95%CI, 31.1-31.8%) new nursing care dependency during the first year post sepsis [44,54]. Within the U.S. Nationwide Inpatient Sample (NIS), Kumar et al demonstrated an increasing need of nursing care after sepsis due to higher survival rates with one third of survivors of severe sepsis being discharged to skilled nursing facilities [55].…”
Section: Nursingsupporting
confidence: 90%
See 2 more Smart Citations
“…The substantial increase in need for nursing between 3 months before and 6 months after sepsis (see Table 3) indicates the burden of disease of both sepsis survivors and their relatives as well the socioeconomic impact on society. Our findings go along with the recent German claims data analysis by Fleischmann-Struzek et al, finding 31.5% (95%CI, 31.1-31.8%) new nursing care dependency during the first year post sepsis [44,54]. Within the U.S. Nationwide Inpatient Sample (NIS), Kumar et al demonstrated an increasing need of nursing care after sepsis due to higher survival rates with one third of survivors of severe sepsis being discharged to skilled nursing facilities [55].…”
Section: Nursingsupporting
confidence: 90%
“…Baseline characteristics such as age [41], percentage of ICU-treatment [41], mean Charlson Comorbidity Index [44] and APACHE II-Score [42] suggest lower disease severity of these cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Es zeigte sich, dass 3 von 4 Sepsisüberlebenden im ersten Jahr nach Sepsis unter neu aufgetretenen psychischen, physischen oder kognitiven Erkrankungen litten, die häufig überlappten 14 .…”
Section: Hintergrundunclassified
“…Among the myriad of new diseases which can be associated with sepsis survival ( 6 ), new chronic care dependency, need for chronic dialysis and inability to breathe without mechanical support can be regarded as particularly crippling conditions. We explored the development of these adverse outcomes, the risk of mortality and the impact of corresponding risk factors using a large database of sepsis survivors identified in nationwide German health claims records of the AOK (Allgemeine Ortskrankenkasse) health insurance, which covers 30% of the German population ( 16 ). The study was registered (DRKS00016340) and approved by the local institutional review board of the Jena University Hospital, Germany (2019-1282-Daten).…”
Section: Introductionmentioning
confidence: 99%